A PROBLEMATICS OF THE SECRET DISCLOSURE OF BANKS BETWEEN STATE INTEREST AND PROTECTION TO CUSTOMERS - Fahrurozi, Rizky (Dialogia Iuridica, 2020)
The objectives of this research are to analyze (1) the definition and scope of bank secrecy; (2) the implementation bank secrecy as a form of legal protection to customers; (3) problematic disclosure of bank secrecy between state interests and protection to customers; (4) bank refusal rights to open bank secrecy. The method used is the normative legal research with the statute and conceptual approaches. The research result indicated (1) the definition of bank secrecy is everything related to information about depositors and their deposits. The scope of bank secrecy relates to information about the depositors and their deposits; (2) the implementation bank secrecy as a form of legal protection to customers consists of preventive and repressive legal protection; and (4) bank refusal rights to open bank secrecy indicates that the bank has the right to refuse to open bank secrets based on the contractual relationship between the bank and its customers. According to Article 1338 of the Civil Code the agreement is binding on the parties who make it, but it is not binding on third parties in this case including the state as a third party.